1998
DOI: 10.1128/jb.180.15.3757-3764.1998
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Resolution of an Experimental Paradox in Bacterial Chemotaxis

Abstract: Escherichia coli responds to its environment by means of a network of intracellular reactions which process signals from membrane-bound receptors and relay them to the flagellar motors. Although characterization of the reactions in the chemotaxis signaling pathway is sufficiently complete to construct computer simulations that predict the phenotypes of mutant strains with a high degree of accuracy, two previous experimental investigations of the activity remaining upon genetic deletion of multiple signaling co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…While E. coli and B. subtilis cells tumble approximately every 3 s, individual E. coli cells are more likely to tumble than B. subtilis ( 17 ). We, therefore, examined the nontumbling, chemotaxis-gutted E. coli strain RBB1050 ( 25 ) and found that it still produced periodic fluid flows with a comparable period to the WT cells (half-period, T 1/2 = 4.6 ± 2 s) (fig. S4), thereby ruling out tumbling as a requirement for periodic flow.…”
Section: Resultsmentioning
confidence: 99%
“…While E. coli and B. subtilis cells tumble approximately every 3 s, individual E. coli cells are more likely to tumble than B. subtilis ( 17 ). We, therefore, examined the nontumbling, chemotaxis-gutted E. coli strain RBB1050 ( 25 ) and found that it still produced periodic fluid flows with a comparable period to the WT cells (half-period, T 1/2 = 4.6 ± 2 s) (fig. S4), thereby ruling out tumbling as a requirement for periodic flow.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli ΔcheY6021 strain KO641 recA (Bourret et al ., 1990) and Δ( cheA‐cheZ )::Zeo R strain RBB1050 (Abouhamad et al ., 1998) have been described previously. The Δ(cheY‐cheZ)4313 strain RP5231 (Liu and Parkinson, 1989) was a gift from J. S. Parkinson (University of Utah).…”
Section: Methodsmentioning
confidence: 99%
“…In cells in which the cytoplasm has been exchanged for buffer (Ravid and Eisenbach, 1984), or in which CheY (Liu and Parkinson, 1989) or CheY and other cytoplasmic chemotaxis proteins have been deleted (Wolfe et al, 1987;Abouhamad et al, 1998), motors spin exclusively CCW. In the former case, switching between CW and CCW states can be induced by the addition of fumarate, which stabilizes the CW state (Prasad et al, 1998).…”
Section: Introductionmentioning
confidence: 99%